Relation of interlobar collaterals to radiological heterogeneity in severe emphysema. Issue 5 (7th February 2006) - Higuchi, T; Reed, A; Oto, T; Holsworth, L; Ellis, S; Bailey, M J; Williams, T J; Snell, G I
Abstract : Background: A study was undertaken to assess the prevalence of interlobar collateral ventilation in patients with severe emphysema to identify factors that may help to predict patients with significant collateral ventilation. Methods: Between April 2002 and August 2003, ex vivo assessment of the lungs 17 consecutive patients with smoking related severe emphysema was performed. To assess collateral flow, all lobes of explanted specimens were selectively intubated using a wedged cuffed microlaryngeal intubation tube and then manually ventilated using a bagging circuit. Interlobar collateral ventilation was defined as the ability to easily inflate a non-intubated lobe at physiological pressures. Pre-transplant demographic characteristics, physiological data, radiological results, and explant histology were assessed for retrospective relationships with the degree of interlobar collateral ventilation in the explanted lung. Results: A total of 23 lungs were evaluated, 15 of which (66%) had significant collateral interlobar airflow. There were no significant differences in any demographic, physiological, or pathological variables between patients with collateral ventilation and those with no collateral ventilation. However, there was a significant relationship between the presence of interlobar collateral ventilation and radiological scores (p<0.05). Conclusions: Interlobar collateral ventilation occurs to a much greater extent in patients with radiologically homogeneous emphysema than in those with heterogeneous emphysema. Heterogeneity of emphysema may predict patients with a significantly reduced risk of interlobar collateral ventilation.